2005
DOI: 10.3354/meps296183
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural flexibility during year-round foraging in macaroni penguins

Abstract: Penguins are major consumers in the marine environment. However, like many top predators, very little information exists on their foraging behaviour outside the breeding season. We investigated the foraging behaviour of the macaroni penguin Eudyptes chrysolophus continuously for 2 consecutive years, from the end of December 2001. This allowed us to investigate whether foraging behaviour varied between sexes, years or phases of the annual cycle. Male penguins tended to dive deeper and longer than female penguin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 59 publications
(75 reference statements)
6
60
0
Order By: Relevance
“…1, 3 & 4) suggest that macaroni penguins target predictable foraging areas in winter, thus concentrating their foraging effort within a restricted part of their potential range and suitable habitats (Wilson 1995, Bost et al 1997. It is also worth noting that none of the tracked birds came ashore during the winter, thus remaining at sea for over ~6 mo, confirming previous studies based on land-based observations (Warham 1975) and winter diving data (Green et al 2005).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…1, 3 & 4) suggest that macaroni penguins target predictable foraging areas in winter, thus concentrating their foraging effort within a restricted part of their potential range and suitable habitats (Wilson 1995, Bost et al 1997. It is also worth noting that none of the tracked birds came ashore during the winter, thus remaining at sea for over ~6 mo, confirming previous studies based on land-based observations (Warham 1975) and winter diving data (Green et al 2005).…”
Section: Discussionsupporting
confidence: 74%
“…1), would reveal whether those birds mix with the birds reported here. In the same way, the winter food and feeding ecology of the huge population of macaroni penguins that breed in South Georgia (southern Atlantic Ocean) remain essentially unknown (but see Green et al 2005), although these birds also seem to be distributed in the PFZ during winter (British Antarctic Survey unpubl. data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been previously shown as a reliable proxy for prey capture during foraging events and correlates positively with bill openings and closings (Ropert-Coudert et al 2001;Simeone and Wilson 2003;Takahashi et al 2004;Bost et al 2007). Because of surface noise, we used a conservative approach and analyzed dives 110 m in depth, which is the suggested depth threshold for foraging dives of macaroni penguins at Bird Island, South Georgia (Green et al 2005).…”
Section: Tdr Data Analysismentioning
confidence: 99%
“…Several of these tracking studies have identified variability in the behaviour of marine fish, turtles, birds and mammals, indicating that this may be a common feature (Folkow et al 2004, Green et al 2005). For example, temporal shifts in behaviour have frequently been recognised at dif-ferent seasonal and/or diel scales.…”
Section: Introductionmentioning
confidence: 99%